Use f(x)= x+8 and g(x)= x+1 To find the following

A. (f+g) (x)= ?

B. (f-g) (x)= ?

C. (fg) (x) = ?

D. (f/g) (x) = ?

Simplify all answers

Use f(x)= x+8 and g(x)= x+1 To find the following

A. (f+g) (x)= ?

B. (f-g) (x)= ?

C. (fg) (x) = ?

D. (f/g) (x) = ?

Simplify all answers

Tutors, please sign in to answer this question.

Middletown, CT

Hi Again Bridget;

A. (f+g) (x)= ?

(f+g)(x)=(x+8)+(x+1)

(f+g)(x)=2x+9

B. (f-g) (x)= ?

(f-g)(x)=(x+8)-(x+1)

(f-g)(x)=7

C. (fg) (x) = ?

(fg)(x)=(x+8)(x+1)

(fg)(x)=x^{2}+8x+1x+8=x^{2}+9x+8

D. (f/g) (x) = ?

(f/g)(x)=(x+8)/(x+1)

Justin H.

Math, Computer Science, and SAT Tutoring from a Google Engineer

Harrison, NJ

5.0
(363 ratings)

Michael E.

H.S. Mathematics Tutor (Certified NJ Teacher)

Saddle Brook, NJ

5.0
(87 ratings)

Christine V.

Math, Portuguese (BR), & Beginner Japanese

Bronx, NY

4.9
(262 ratings)

- Algebra 1 3517
- Math 7991
- Algebra 4344
- Math Help 4593
- Precalculus 1322
- Algebra Word Problem 2194
- Word Problem 4422
- Algebra Help 925
- Geometry 1606
- Algebra 2 Question 456